Species Compositiom and Distribution of Seaweeds at Thi Nai Lagoon, Binh Dinh Province - Tien, Dam Duc (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 4DO - 10.25073/2588-1140/vnunst.4691, 2017)
This paper presents results on species composition and distribution of seaweeds at Nai lagoon, Ninh Thua province from 2013 until 2014 at 12 sites was showed that, at Nai lagoon area we was recording 43 species of marine seaweeds, they are belonging to four divisions, as: Cyanophytes , Rhodophytes , Phaeophytes and Chlorophytes . Among them, eight species are classified in Cyanophytes (comprising 18.6% of total species); eleven species in Rhodophytes (25.6%); four species in Phaeophytes (9.3%) and twenty two species in Chlorophytes (46,5%). The species composition of marine seaweeds from Thi Nai lagoon show significant differences in the species composition as follows: 8 species (side number 4, 13 and 18) to 21 (side number 10) and average value is 12.2 species per side. The number species at dry season is 40 and rainy season is 30 (there are 30 species in of boots dry and rainy seasons) Coefficient homogeneous is oscillating from 0.10 (side number 4 and 5) to 0.66 (5 and 7). The current investigations show that 39 species of 43 species were collected in the littoral zone and 35 species in sub-littoral zone (31 species are distributing in both the tide and the sub tide). Marine algal flora in Thi Nai lagoon is represented by tropical elements as defined by Cheney.